Perkembangan Sistem Informasi pada Organisasi Dakwah - Erwan Efendi; Rahayu Nian Ramadhani,; Aidil Zihad,; Pradana Arya Dewangga D, (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Information systems have a very important role, the more rapidly the development of a company or organization, the information system also has an increasingly important role. The demand for an increasingly good information system is the result of demands for company development, technological developments, government policies, changes in procedures and demands for information needs. Information system development is often referred to as the system development process (system development). Information system development is defined as an activity to produce computer-based information systems to solve organizational problems or take advantage of opportunities that arise. System development can mean compiling a new system to replace the old system as a whole or repairing an existing system, this is done because the previous system has problems, inefficient operations, and so on. Methods In this study using a qualitative approach to the method of interviewing informants who are considered related to the problem. Data collection by providing a number of questions that can answer the formulation of the problem in this mini research. In writing the report on the results of this mini research using various references related books and journals. Keywords :information, organization, dakwah